2018
DOI: 10.1002/da.22857
|View full text |Cite
|
Sign up to set email alerts
|

Impaired generalization of reward but not loss in obsessive-compulsive disorder

Abstract: Background: Generalizing from past experiences can be adaptive by allowing those experiences to guide behavior in new situations. Generalizing too much, however, can be maladaptive. For example, individuals with pathological anxiety are believed to overgeneralize emotional responses from past threats, broadening their scope of fears. Whether individuals with pathological anxiety overgeneralize in other situations remains unclear. Methods: The present study (N = 57) used a monetary sensory preconditioning par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
10
3
Order By: Relevance
“…Our modeling results also appear not consistent with the result of a study examining generalization in OCD patients [36]. Using sensory preconditioning paradigm with monetary rewards and losses, this study reported that OCD patients generalized less from rewards, but not losses, than heathy controls (HCs).…”
Section: Limitations and Perspectivescontrasting
confidence: 99%
See 1 more Smart Citation
“…Our modeling results also appear not consistent with the result of a study examining generalization in OCD patients [36]. Using sensory preconditioning paradigm with monetary rewards and losses, this study reported that OCD patients generalized less from rewards, but not losses, than heathy controls (HCs).…”
Section: Limitations and Perspectivescontrasting
confidence: 99%
“…Using sensory preconditioning paradigm with monetary rewards and losses, this study reported that OCD patients generalized less from rewards, but not losses, than heathy controls (HCs). Looking at their results, in fact the HCs did not on average show significant generalization from rewards but showed chance-level choices, and the OCD patients significantly avoided the stimulus associated with a second stimulus that was later associated with stochastic (risky) gain and preferred the alternative stimulus associated with a second stimulus later associated with neutral outcome (Figure 3a of [36]). In the second-stimulus-outcome (gain/loss/neutral) association phase of the task, participants were required to "bid" on the presented stimulus and received feedback regardless of their bidding decisions, whereas no feedback was given in the final choice phase of the task.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Natural stimuli rarely appear in exactly the same form from encounter to encounter, therefore, the ability to generalize learning across stimuli and contexts is essential for adaptation. Impaired reward generalization 22 and excessive fear generalization 41 which lead to maladaptation are linked to anxiety-like behaviours. Previous research suggests that mPFC and BLA may play a role in both positive and negative emotions, but whether and how their monosynaptic connection governs reward generalization and modulate anxious states is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting these BLA neurons remarkably supports positive reinforcement 7 . Given the impairment of reward generalization on some individuals with pathological anxiety 22 and the anxiolytic effect of the posterior part of BLA (pBLA) 23 , it will be valuable to explore whether and how the distinct pBLA neurons with their associated circuits necessarily lead to reward generalization and promote stress resilience to ameliorate anxiety- and depression-like behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are other indications that OCRDs, DABs, and ICDs (the prototypical "compulsive," "addictive," and "impulsive" disorders), tend to show some overlap in terms of their underlying "motivations." For instance, few studies suggest that OCD patients (whose behaviors are thought to be typically maintained by negative reinforcement) may report greater anhedonia, [44][45][46] lower reward generalization, 47 and increased reward expectancy from their compulsions, 28,48 which can also be performed harshly. 49 Of note, rewarding and/or impulsive features in OCD have been associated with a range of poor outcomes, from greater duration of illness 49 to worse response to SRIs.…”
Section: Discussionmentioning
confidence: 99%